Experimental–numerical investigation of momentary discomfort in a high-speed train in varying wind speed conditions. Issue 4 (3rd April 2022) - Liu, Dongrun; Li, Tian; Lu, Zhaijun; Chen, Jun; Zhong, Mu
Abstract : Understanding the effect of wind speed variation on wind-induced momentary discomfort is the basis to improve the train vibration comfort. This study focuses on this challenge. Firstly, the momentary discomfort evaluation index Pw is developed and proved by the full-scale test. Then, setting Pw as the critical value, a multi-body nonlinear numerical investigation of the effect of the wind speed change rate, peak-wind speed duration, and wind speed variation amplitude on momentary discomfort in a train is conducted. Furthermore, the unfavourable wind speed variation condition for the wind-induced momentary discomfort in the train is obtained. Results indicate that the most intense condition for the train vibration momentary discomfort appears when the change rate of wind speed is faster and the duration of the peak wind drives the car-body rolling to the limit position. Consequently, critical wind speed for the wind-induced momentary discomfort in changing wind speed conditions is proposed, which provides a reference for an efficient train operation scheme to improve vibration comfort in a train under wind speed variation conditions.